Exploradores de libros estrategia didáctica para fomentar la lectura en estudiantes de grado primero (2024)
The primary objective of this research project, titled "Book Explorers: Teaching Strategy to Promote Reading in First Grade Students," is to promote the reading habit in first grade students of the Liceo Del Caribe, through a didactic strategy that involves both children and their families.